Analisis Faktor Yang Mempengaruhi Masyarakat Muslim Melakukan Wakaf Saham - Anwar Sahal (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
Abstract: The purpose of this research is to analyze the factors of product knowledge, Islamic religiosity, consumer attitude, trust, intention, and consumer behavior that influencing Moslem societies in contributing to the waqf of shares. This research uses survey data from questionnaires which distributed to 220 respondents who live in areas of DKI Jakarta, Bogor, Depok, Tangerang, and Bekasi. Respondent data is processed using SEM analysis method which supported by Smart PLS application. The result of this research shows that the factors of product knowledge and trust are not significant influence on intention factor of Moslem societies in contributing on waqf of shares. Islamic religiosity and consumer attitude factors have positive and significant influence on intention factor. Meanwhile, intention factor has positive and very significant influence on consumer behavior factor with a statistic value of 22,963. Suggestions based on research result: first, it is necessary to hold a literacy and education program for Moslem societies in order to the understanding and knowledge of Moslem societies about waqf of shares are better. Second, it is necessary to hold a certification program for nazhir so that Moslem societies’ trust in nazhir increases. Keywords: Moslem Societies, Intention, Waqf of Shares.